2019
DOI: 10.1177/0363546519849476
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Return to Sport After High Tibial Osteotomy: A Directed Acyclic Graph Approach

Abstract: Background: High tibial osteotomy (HTO) is increasingly used in young and physically active patients with knee osteoarthritis. These patients have high expectations, including return to sport (RTS). By retaining native knee structures, a return to highly knee-demanding activities seems possible. However, evidence on patient-related outcomes, including RTS, is sparse. Also, time to RTS has never been described. Furthermore, prognostic factors for RTS after HTO have never been investigated. These data may furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
0
29
1
1
Order By: Relevance
“…20 Also, rates of return to sport (RTS) of 82 to 85% and return to work (RTW) of 85 to 95% have been reported after HTO. [21][22][23] Knee joint distraction (KJD) is a less well known but promising alternative joint-sparing treatment option in relatively young OA patients with severe complaints. With KJD, an external distraction device creates a temporary load reduction between focal areas of cartilage surfaces in the knee.…”
mentioning
confidence: 99%
“…20 Also, rates of return to sport (RTS) of 82 to 85% and return to work (RTW) of 85 to 95% have been reported after HTO. [21][22][23] Knee joint distraction (KJD) is a less well known but promising alternative joint-sparing treatment option in relatively young OA patients with severe complaints. With KJD, an external distraction device creates a temporary load reduction between focal areas of cartilage surfaces in the knee.…”
mentioning
confidence: 99%
“…Sports activity level is an important factor in determining MOWHTO. 14 It is also a factor that could be closely associated with MME. Furthermore, there might be other factors that were not identified in the current study that influence PROM after HTO.…”
Section: Discussionmentioning
confidence: 99%
“…Hoorntje et al have reported that among 294 patients who underwent HTO, the rate at which patients returned to sporting activities was 82%, with a rate of returning to sports within 6 months post-operatively of 75% and a rate of returning to sports within 1 year post-operatively of 92%. In a logistic regression analysis, the significant prognostic factor for returning to sports activity was continued sports participation during the year before surgery [ 6 ]. In a recent study of the Japanese population, Kanto has reported that among 77 patients who underwent OW-HTO, the rate of patients who returned to sports was 89.6% (69 patients), with a mean return time of 8.7 ± 2.7 months.…”
Section: Discussionmentioning
confidence: 99%